EFFECTIVE MANAGEMENT CLASS CONCEPT (Case Study: Student Behavior Problematics) - Bambang Afriadi (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2018)
The effectiveness of the learning process is part of good classroom management. But be aware that every individual in the class (student) does not have a homogeneous but heterogeneous character. Implementation of classroom management will encounter various inhibiting factors. Reviews These barriers can come from teachers Themselves, from students, the family environment, and or because of the facilities. The condition of teaching and learning will be sustained while teachers during the process of concentration can maintain student learning and student behavior. Therefore, management in the class Becomes important to be Discussed, and found the solution. In writing this article using research literature from various sources related to this topic related to the subject.